Pengaruh Pasir Batu Kapur Sampang Madura sebagai Agregat Halus terhadap Slump Beton - Gono, Theresia Kristanti; Sutriono, Bantot; Rochmah, Nurul (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Concrete is one of the most widely used construction materials, with aggregates forming the largest portion of its total volume. The growing demand for natural aggregates encourages the exploration of alternative materials that are more sustainable and locally available. Limestone from the Sampang–Madura region is considered a potential aggregate substitute, although its distinct physical characteristics require detailed investigation. This study examines the effects of incorporating limestone as a 50% replacement for coarse aggregate and as a fine aggregate substitute at variations of 0%, 5%, 10%, 15%, and 20%. Experimental testing was carried out using cylindrical specimens measuring 15×30 cm with a target strength of f’c 25 MPa. The tests included slump testing,. The results indicate that replacing fine aggregates with up to 20% limestone still meets the required slump range, although mixtures with substitutions of 10% or more show reduced workability due to the high absorption capacity of limestone, which affects the water–cement ratio. Overall, the findings demonstrate that local limestone can serve as a viable aggregate substitute, reducing dependence on natural aggregates while supporting environmentally sustainable construction practices.